Reflections on the courses of Teacher Training in Peru and Brazil - Chávez Hernani, María (2020)
This article presents a comparative analysis between the Pedagogical Projects of the initial teacher training courses of the Faculty of Education of the National University of San Marcos - UNMSM (Peru) and the Federal University of Rio Grande - FURG (Brazil). The research developed was qualitative, performed through documentary analysis. Documents from the two participating universities were analyzed, seeking to verify aspects such as objectives for teacher training, training approach, professional profile, duration of courses, developed disciplines and pre professional practice. It is possible to perceive after the analysis of both pedagogical projects that seek the formation of a professional committed to learning, so that it is a leader in education with initiative, creativity, with an integral vision of the educational sector and a solid theoretical and practical formation.